Predictors of PTSD Improvement with Cognitive/Exposure Group Interventions in Operation Enduring Freedom/Operation Iraqi Freedom Female Veterans. Issue 4 (19th May 2017) - Falkenstein, Martha J.; C'de Baca, Janet; Belon, Katherine; Castillo, Diane T.
ABSTRACT: Predictors of successful PTSD outcome have been examined through individually delivered treatments. We examined predictors using a group protocol with cognitive, exposure, and skills modules. Assessments included self-report and interview (CAPS, SCID-I/II) measures at baseline, post, and six months; treatment was a 16-week, three-member group for 32 OEF/OIF women Veterans. A regression analysis showed major depressive disorder and no baseline psychiatric medication predicted PTSD improvement. PTSD improvement predicted fewer outpatient medical visits at follow-up. The results supported past research and challenged other findings (e.g., sexual assault predicts less improvement). An additional unique contribution was examining predictors in a group treatment format.